An exploration of the role of toxic workplaces and burnout amongst social workers in Cape Town - Manqindi, Zodwa (Department of Social Development, 2025)
Social Workers in Cape Town operate within high-pressure environments characterised by complex social issues, limited resources, and emotionally intense workloads. These conditions often give rise to toxic workplace dynamics, including poor leadership, lack of emotional support, excessive caseloads and organisational dysfunction (September and Dinbabo, 2008; Matlakala, 2022). The purpose of this study was to explore the role of toxic workplaces and burnout amongst Social Workers in Cape Town. The primary objective was to develop an in-depth understanding of the experiences, challenges, and coping strategies of Social Workers in workplaces where leaders behave negatively, that result in Social Workers experiencing burnout. The secondary objective was to engage practitioners' opinions as to what can be done to mitigate toxic environments in the workplace. A qualitative exploratory research design was employed to achieve these objectives. In-depth semi-structured interviews were undertaken with 18 Social Workers working in Non-profit Organisations in Cape Town. The findings revealed that Social Workers face heavy workloads, fast-paced environments, unsafe areas, inadequate resources, and lack of supervision, all of which impact their Mental Health and Well-being. Common problems included micromanagement, unmanaged caseloads, poor leadership, nepotism, gaslighting, disrespect, and lack of appreciation. Additionally, ineffective leadership characterised by a lack of transparency, unity, and ineffective styles was noted. Participants suggested that founders of private organisations should have social work experience to better support employees. The findings of the study also stressed the impact of toxic workplaces on social workers, including mental health struggles, with many coping through medication, alcohol, or smoking. High turnover rates were attributed to burnout, underperformance, absenteeism, feeling underpaid, and mistreatment. Decisions to stay or leave were influenced by personal circumstances and mental health priorities. In summary, these findings highlight the need for better leadership, support systems, and mental health resources to improve the work environment for Social Workers.